When do satisfied employees become more committed? A multilevel investigation of the role of internal service climate. (September 2019) - Wong, IpKin Anthony; Ma, Erdan; Chan, Suk Ha Grace; Huang, GuoQiong Ivanka; Zhao, Tong
Highlights: This study reveals a relationship between job security and organizational commitment, by considering job satisfaction and perceived health. It highlights the importance of the cross-level boundary condition of internal service climate (ISC) at the organizational level. The satisfaction effect is more salient in low ISC organizations, while the health effect is only significant in low ISC organizations. Abstract: The objective of the study is to improve the current understanding of frontline employee perceptions of health by investigating the role of job security and satisfaction. The linkage between perceived health and organizational commitment is also explored. This study further tests the cross-level moderating effect of internal service climate based on a multilevel design. Based on a multilevel study that involved 1251 employees, including both frontline employees and supervisors from 29 casinos, results reveal that the relationship leading from job security and job satisfaction to organizational commitment through perceived health is contingent on organizational-level service climate; and the relationship is more salient for casinos with low-quality internal service climate. Theoretical and managerial implications are presented in the study.